Pelatihan Mindful Parenting untuk Mengurangi Stres Pengasuhan Pada Orang Tua Dari Anak Dengan Spektrum Autisme - Boby, Kurnia; Ginanjar, Adriana Soekandar; Pranawati, Santy Yanuar (Universitas Muhammadiyah Metro, 2024)
This study involved a mindful parenting training program to reduce parenting stress levels in parents of children with autism spectrum disorder (ASD). The research design utilized a quasi-experimental perspective, involving 20 parents of children aged 12-18 years who had received an ASD diagnosis at least two years prior. Parenting stress levels are evaluated by comparing pre-test, post-test, and follow-up scores using the Parenting Stress Index (PSI). The studies showed a noteworthy reduction in parenting stress after mindful parenting training. Furthermore, analysis of qualitative data suggested that parents of children with ASD exhibited enhancements in self-regulation, mindfulness, acceptance of their parental roles, more adaptive emotional responses, decreased stress, and improved mental well-being.